Study on call admission control schemes in 3GPP LTE network - Maniru Malami Umar; Aminu Mohammed; Abdulhakeem Abdulazeez; Solomon Ordeun Yese (Association for Scientific Computing Electronics and Engineering (ASCEE), 2020)
Call admission control (CAC) is a process of accepting new calls or handoff calls in a network while regulating the Quality of Service (QoS) of existing or active calls without degrading any call drop. CAC is an RRM technique and directly impacts QoS for individual connection and the overall system efficiency. This paper presents a short review of some existing CAC schemes proposed for the 3GPP LTE network. The review aims to guide researchers to know what CAC is, how it operates, and its benefits to the overall system performance. The schemes reviewed can be classified based on the aim they were proposed, such as guaranteeing QoS of calls, increasing the utilization of available network resources, reducing call blocking, and call dropping probabilities. The paper further summarised all reviewed schemes by highlighting each scheme's operations, strengths, and weaknesses.